PSYCHOLOGY OF STUDYING FOREIGN LANGUAGE IN THE NON-LINGUISTIC SPECIALTIES OF THE UNIVERSITY - Bekzhigitova, Z.S.; Bakenova, A.M.; Alzahrani, K.A. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2015)
Current article investigates psychological features which have to be considered when foreign languages are studied on the non-linguistic specialties.
Keywords: psychology; methodic of foreign language teaching; individual; individual abilities; motivation; comprehension; organization; non-linguistic specialties; higher education